Genetic analysis of feet and legs in Nelore cattle - Vargas, Giovana [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to estimate variance components of two traits associated to feet and legs in Nelore cattle and identify putative genomic regions underlying the expression of these traits through genome-wide association (GWA) analyses. Feet and legs was evaluated by the assignment of visual scores at two different moments: FL1) binary trait measured at yearling (about 550 days of age), aimed to identify whether an animal had defects related to feet and legs (FL1=1) or not (FL1=0); FL2) feet and legs score ranging from 1 (less desirable) to 5 (more desirable) was assigned to the top 20% animals for the selection index adopted by the beef cattle breeding program PAINT (CRV Lagoa), which were measured around 2-5 months after the evaluation of yearling. The FL1 and FL2 traits were evaluated together with yearling weight (YW). The components of variance and covariance and breeding values were estimated by Bayesian inference, using two-trait animal models (three analyses: FL1-FL2, YW-FL1 and YW-FL2). The genome-wide association (GWA) analyses for FL1 and FL2 was performed using the weighted single-step GBLUP method, from which were estimated the SNP effects. Functional annotation was focused on the ten 1Mb windows explaining the largest fraction of the genetic variance for each trait. Posterior means (standard errors) of heritability estimates were equal to 0.18 (0.04) and 0.39 (0.07), for FL1 and FL2, respectively. The estimate of genetic correlation between FL1 and FL2 (-0.47) was of moderate magnitude and negative, as expected considering that the classification score that favors each trait represents numerical values assigned in opposite directions. The genetic correlation estimated between FL2 and YW (0.39) suggests that the average yearling weight of the studied population is currently not high enough to cause a negative association with feet and legs problems. The genetic trends estimated for FL1 and FL2 (-0.043 and ...

O objetivo deste estudo foi estimar os componentes de variância para a característica aprumo em bovinos da raça Nelore, e realizar estudos de associação genômica ampla para identificar possíveis regiões genômicas relacionadas com sua expressão. Os registros de aprumo foram obtidos pela atribuição de escores visuais em dois momentos diferentes: FL1) característica binária medida ao sobreano, com o objetivo de identificar se o animal apresenta (FL1=1) ou não (FL1=0) defeito de aprumo; FL2) escores de aprumo variando de 1 (menos desejável) a 5 (mais desejável), foram designados aos animais top 20% para o índice de seleção adotado pelo programa de melhoramento genético de bovinos de corte PAINT (CRV Lagoa), e foram medidos em torno de 2 a 5 meses após a avaliação de sobreano. As características FL1 e FL2 foram avaliadas em conjunto com peso ao sobreano (YW). Os componentes de variância e covariância e os valores genéticos foram estimados por inferência Bayesiana, por meio de modelo animal bi-característica (três análises: FL1-FL2, YW-FL1 e YW-FL2). O estudo de associação genômica ampla (GWAS) para FL1 e FL2 foi realizado utilizando o método weighted single-step GBLUP, a partir do qual foram estimados os efeitos dos SNPs. As janelas top 10 de 1 Mb que explicam a maior proporção da variância genética foram observadas para cada característica. As médias (erros padrão) a posteriori das estimativas de herdabilidade foram iguais a 0,18 (0,04) e 0,39 (0,07), para FL1 e FL2, respectivamente. A estimativa de correlação genética entre FL1 e FL2 (-0,47) foi de moderada magnitude e negativa, conforme esperado, considerando que o escore de classificação que favorece cada característica corresponde a valores numéricos atribuídos em sentidos opostos. A correlação genética estimada entre FL2 e YW (0,39) sugere que a média do peso ao sobreano da população em estudo não é alta a ponto de causar ...
Keywords: Bovino de corte; Nelore (Zebu); Cromossomos; Teoria bayesiana de decisão estatistica; Genetica animal; Membros anteriores; Membros posteriores; Animal genetics